Phylogenetic position and independent generic status of Indocypraea (Asteraceae-Heliantheae-Ecliptinae): evidence from chloroplast DNA sequences - Ren, Chen (Phytotaxa, 2016)
Indocypraea (Asteraceae-Heliantheae-Ecliptinae) is a newly-erected monotypic genus, containing only I. montana. Historically, this species has been variously included in Verbesina, Wedelia, and Wollastonia, and its position has never been investigated from a molecular phylogenetic perspective. Based on chloroplast DNA sequences, I revealed that I. montana is only remotely related to these genera, and is sister to Synedrella with strong support. This topology is also significantly favored by the statistical topology tests. The generic status of Indocypraea is further supported by the achenes brownish yellow and densely dotted with white or yellowish white mottles, and a base chromosome number of x = 37, both of which are distinct in the subtribe Ecliptinae. Additionally, I clarify the identity of Wedelia wallichii var. megalantha, and synonymize it with I. montana.